Students' Educational Background and Arabic Reading Skills (Maharah Qira’ah): A Qualitative Study of Tenth-Grade Students at MAN 1 Medan: Al Khalfiyyah Al Talimiyyah lil Tullab wa Maharah Al Qiraah Al Arabiyyah Dirasah Nawiyyah lada Tullab Al Saff Al Ashir fi Al Madrasah Al Aliyah Al Hukumiyyah Al Ula Medan - Izzatul Munawaroh Siregar; Harun Al Rasyid (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study examines how students' educational backgrounds shape Arabic reading skills (maharah qira’ah) among tenth-grade students at MAN 1 Medan. Using a descriptive qualitative design, data were collected through classroom observation, interviews, and documentation. The informants were an Arabic teacher, a homeroom teacher, and students representing SMP, MTs, and pesantren backgrounds. Documentation of 229 student responses was used to map school origin. The findings show that MTs and pesantren graduates generally have stronger initial readiness in pronunciation, vocabulary recognition, text comprehension, and reading confidence. SMP graduates need more basic scaffolding in identifying Arabic letters, vowel marks, and simple meanings. However, motivation, vocabulary mastery, peer support, teacher strategy, and repeated reading practice enable several SMP graduates to improve. The study recommends differentiated instruction through diagnostic reading, vocabulary scaffolding, graded reading, and peer tutoring. تهدف هذه الدراسة إلى تحليل علاقة الخلفية التعليمية بمهارة القراءة العربية لدى طلاب الصف العاشر في المدرسة العالية الحكومية 1 ميدان. اعتمدت الدراسة المنهج الوصفي النوعي، وجمعت البيانات من خلال الملاحظة الصفية، والمقابلات، والوثائق المدرسية. شملت المقابلات معلما للغة العربية، وولي صف، وثلاثة طلاب يمثلون خلفيات SMP وMTs والمعهد الإسلامي. كما استخدمت الدراسة توثيق 229 استجابة حول أصل المدرسة. أظهرت النتائج أن طلاب MTs والمعاهد يمتلكون استعدادا أوليا أفضل في النطق، وفهم المفردات، واستيعاب النصوص، والثقة في القراءة. أما طلاب SMP فيحتاجون إلى دعم أساسي في التعرف إلى الحروف والحركات والمعاني البسيطة. ومع ذلك، تسهم الدافعية، وإتقان المفردات، ودعم الأقران، واستراتيجية المعلم، والتدريب المتكرر في تحسين مهارة القراءة. وتوصي الدراسة بالتعليم التفاضلي القائم على التشخيص الأولي، وتقوية المفردات، والتدريب المتدرج، والتعلم التعاوني. Penelitian ini menganalisis hubungan latar belakang pendidikan siswa dengan keterampilan membaca bahasa Arab (maharah qira’ah) pada siswa kelas X MAN 1 Medan. Penelitian menggunakan desain deskriptif kualitatif melalui observasi kelas, wawancara, dan dokumentasi. Informan terdiri atas guru bahasa Arab, wali kelas, serta siswa yang mewakili latar belakang SMP, MTs, dan pesantren. Dokumentasi 229 respons siswa digunakan untuk memetakan asal sekolah. Hasil penelitian menunjukkan bahwa lulusan MTs dan pesantren umumnya lebih siap dalam pelafalan, penguasaan kosakata, pemahaman teks, dan keberanian membaca. Lulusan SMP memerlukan pendampingan dasar dalam mengenali huruf, harakat, dan makna sederhana. Namun, motivasi belajar, mufradat, dukungan teman sebaya, strategi guru, dan latihan berulang dapat mempercepat perkembangan maharah qira’ah. Penelitian merekomendasikan pembelajaran diferensiatif melalui diagnosis awal, penguatan kosakata, latihan bertahap, dan tutor sebaya.